2016
DOI: 10.1186/s12891-016-1108-6
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritic changes rather than age predict outcome following arthroscopic treatment of femoroacetabular impingement in middle-aged patients

Abstract: BackgroundOur purpose was to evaluate outcome following arthroscopic treatment of femoroacetabular impingement (FAI) in middle-aged patients and to define risk factors for conversion to total hip arthroplasty (THA).MethodsThis was a retrospective case series of 79 consecutive patients (40 to 65 years) undergoing arthroscopic treatment of FAI (follow-up ≥12 months). Outcome at follow-up was assessed using Hip outcome score (HOS). Alpha angle, Kellgren Lawrence grade (K-L grade), joint space width (JS), lateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Although age is commonly cited as an association with conversion to THA, Herrmann et al. 23 suggested from their retrospective series of middle-aged patients that age as a sole factor should not be prohibitive of hip arthroscopy, but rather osteoarthritic changes as documented by Kellgren Lawrence grade 3 or joint space width <2 mm. The likely independent influence of degenerative changes is confirmed by a statewide study of hospitals in New York that found both age >60 years and the presence of pre-existing arthritis to be independent risk factors for THA conversion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although age is commonly cited as an association with conversion to THA, Herrmann et al. 23 suggested from their retrospective series of middle-aged patients that age as a sole factor should not be prohibitive of hip arthroscopy, but rather osteoarthritic changes as documented by Kellgren Lawrence grade 3 or joint space width <2 mm. The likely independent influence of degenerative changes is confirmed by a statewide study of hospitals in New York that found both age >60 years and the presence of pre-existing arthritis to be independent risk factors for THA conversion.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also shown that prior hip arthroscopy or surgeries have been associated with predictors of clinical outcomes, 14 , 31 whereas the present study did not note prior hip arthroscopy as a significant predictor of conversion, despite it being statistically significant. Additional factors previously associated with conversion have been worsening preoperative evidence of arthritic changes or chondral damage 20 , 22 , 23 , 25 , 26 , 28 , 33 , 34 , 35 or acetabular morphology. 36 Contralateral THA has also been associated with increased conversion to THA after hip arthroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…R educed hip joint space measurements have been shown to predict early conversion to total joint arthroplasty after hip arthroscopy. [1][2][3][4] In the article titled "Standardizing the Pre-Arthritic Hip Joint Space Width: An Analysis of 994 Hips," the authors Kraeutler, Garabekyan, Goodrich, Fioravanti, Chadayammuri, and Mei-Dan 5 analyzed the radiographs in a large population. Joint space and lateral center edge angle were measured on standing anteroposterior radiographs in both symptomatic and asymptomatic individuals.…”
Section: See Related Article On Page 2114mentioning
confidence: 99%
“…10 However, the early conversion rate to total hip arthroplasty may increase in more disadvantageous study cohorts, for example, up to 23% in middle-age patients between 40 and 65 years of age. 50 Patients with preoperative radiographic findings of moderate or advanced osteoarthritis, a radiologic joint space < 2 mm, advanced cartilage defects, presence of a subchondral acetabular edema with cystic changes on MRI, and hip dysplasia with a lateral center-edge angle < 20 degrees revealed poorer outcomes and were associated with a higher likelihood of early Fig. 7 (a-c) Ongoing hip joint degeneration with consecutive osteoarthritis on a (a) 3.5-year postoperative anteroposterior conventional radiograph in a 36-year-old male patient compared with (b) intraoperative and (c) preoperative conventional radiographs.…”
Section: Osteoarthritismentioning
confidence: 99%
“…26,[51][52][53][54] Thus arthroscopic and open hip joint preservation surgery should be considered as a relative contraindication in these patients. 26,50,51…”
Section: Osteoarthritismentioning
confidence: 99%